Evaluation of Drug-Related Receptors in Children With Dilated Cardiomyopathy - Qing Guo; Jie Liu; Peng Zhu; Yali Liu; Nianguo Dong; Jiawei Shi; Hua Peng (Frontiers Media S.A., 2019)
Background: Effective treatments for pediatric dilated cardiomyopathy (DCM) are limited. Currently, pediatric DCM therapy mainly includes supportive heart failure (HF) treatment. While the treatment for child DCM patients is generally the same as that for adult DCM patients, few randomized prospective studies on the clinical efficacy of treatments for pediatric DCM have been published. We explored the appropriate treatments for child patients.Methods: The ultrastructure of pediatric DCM and control hearts was analyzed by electron microscopy and HE staining. Left ventricular tissues from children in the DCM and control groups were subjected to quantitative RT-PCR (qRT-PCR) to study the mRNA expression of receptors related to various treatments, including drugs targeting the renin-angiotensin-aldosterone system (RAAS) system, digoxin, milrinone, and β-receptor blockers, in child patients in the clinic. Furthermore, the differences in drug receptors in heart tissues between children and adults with DCM were analyzed.Results: Compared with the control children, the children in the DCM group showed marked abnormalities in structure and organelles. The mRNA levels of angiotensin-converting enzyme (ACE), REN, prorenin receptor (PRR), NEP, ATP1A1, and phosphodiesterase3 (PDE3A) were higher in the pediatric DCM group than the control group. Interestingly, the mRNA expression of these treatment-related receptors was much higher in children than in adults.Conclusion: ACE inhibitors, PRR or REN receptor inhibitors, PDE3 inhibitors and LCZ696 may be effective in children with DCM. However, β-receptor blockers are not valid treatments for pediatric DCM. Moreover, high receptor expression was observed in children. These data will improve the selection of drugs for DCM patients, enhance treatment, and increase the survival rate.